Local Wisdom Media-Based Learning Model: Basic Competencies for Creative Economy Development in Social Sciences Subjects (Social Sciences) - Sudiadicita Panjaitan; Efendi Napitupulu; Sugiharto Sugiharto (Randwick International of Education and Linguistics Science Journal, 2024)
This research was motivated by the low learning outcomes of students in social studies learning in Class IX of SMP Negeri 1 Pahae Julu on Basic Competencies for Creative Economy Development. The aims of this research are 1) to find out the local wisdom-based learning model that has been developed and is valid for use in the social studies subject for Class IX of SMP Negeri 1 Pahae Julu, and 2) to find out the local wisdom-based learning model that can be developed and can be effective in improving student learning outcomes in the Social Sciences subject for Class IX of SMP Negeri 1 Pahae Julu. The research results show that the "IASUDE" learning model based on local wisdom received an average percentage of 90% validation from design experts, 90% from media experts, and 87.37% from material experts, which can be categorized as very appropriate. The results of the hypothesis test show that the research data have been declared normal and homogeneous. The results of the hypothesis test show that the value of tcount > ttable = -9.51> -1.67, so it can be concluded that tcount > ttable, which means that H1 is accepted, which reads: The IASUDE learning model developed is able to effectively improve the learning outcomes of class IX students at SMP Negeri 1 Pahae Julu.